Pokazateli sorevnovatel'noi nagruzochnosti proizvol'nykh programm figuristok vystupavshikh v chempionate mira 1996 goda - Absalyamova, I. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to determine the parameters of women free skating's loadings at the World Figure Skating Championship in Canada-1996. The loadings had been identified in arbitrary units. At the same time some quantitive characteristics had been taken into consideration: - the total number of elements in programme; - the proportion of differently difficult jumps in programme; - the number of rotations in jumps. 24 participants of the Championships acted as subjects. The data of general and everage difficulties of elements and free programmes, as well as the data of coordinational difficulty of jumps, are analysed and discussed in the paper.